Childhood adiposity, adult adiposity, and the ACE gene insertion/deletion polymorphism: evidence of gene-environment interaction effects on adult blood pressure and hypertension status in adulthood - Sun, C; Ponsonby, A-L; Carlin, JB; Bui, M; Magnussen, CG; Burns, TL; Lehtimaki, T; Wardrop, NH; Juonala, M; Viikari, JSA; Venn, AJ; Raitakari, OT; et al. (Lippincott, Williams and Wilkins, 2018)
Background Genetic variants may modify the associations of adiposity measures with blood pressure (BP) and hypertension. The insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene is an attractive candidate. Aims To examine interaction effects between I/D polymorphism and adiposity measures (BMI, waist circumference, waist-to-hip ratio, and skinfold thickness) during childhood and adulthood in relation to adult BP and hypertension. Methods Data were available for 4835 participants from three prospective cohort studies. Multivariable linear regression models for adult SBP and DBP, and multivariable logistic regression models for hypertension were fit that included interaction effects between child or adult adiposity and I/D polymorphism. Results Evidence for interaction effects on BP/hypertension were found across the three studies. Compared with childhood measures, the effect modification appeared to be more consistent when using adult adiposity. In particular, the adverse effects of greater adult waist circumference on increasing adult SBP and DBP appeared to be larger among carriers of ACE DD (or GG) [adjusted linear regression coefficients 0.26, 95% CI (0.21–0.31) and 0.28 (0.24–0.32) for SBP and DBP, respectively] and ID (or AG) genotypes [0.25 (0.21–0.29) and 0.25 (0.21–0.28), respectively], whereas those with II (or AA) genotypes had smaller effects [0.15 (0.09–0.21) and 0.19 (0.13–0.23)]. Conclusion ACE genetic variation may modify the effect of adult adiposity on increasing BP and risk of hypertension in adulthood. Individuals with ACE DD (or GG) and/or ID (or AG) genotypes, compared with those with II (or AA) genotype, appear more vulnerable to the impact of excess adiposity.